Neural Bases of Brand Reputation Effect on Extension Evaluation: An ERPs Study - Liu, Chang; Song, Zhijie; Shi, Rui (Frontiers in Neuroscience, 2021)
Brand extension, as a marketing strategy, is frequently utilized by enterprises to produce new products. There exist several critical factors determining its success, such as brand reputation and perceived fit. The present study adopts the event-related potentials (ERPs) method to explore the underlying neural mechanism of the joint influence of the two factors on consumers’ evaluation of brand extension. Specifically, consumers were presented with a brand with corporate social responsibility (CSR) or corporate ability (CA) reputation, following attached to an extension product (high fit vs. low fit). And then, they were given a 5-point scale to report their acceptance intention (AI) toward the brand extension. Behavioral data showed a higher AI and a shorter reaction time for high fit in contrast to low fit conditions. For low fit conditions, consumers were more inclined to accept the extension product with a brand with CSR than CA reputation. Neurophysiologically, CSR reputation evoked a larger P2 amplitude and LPP amplitude than CA reputation. Moreover, the low fit conditions elicited a more positive LPP amplitude than the high fit conditions in the context of a brand with a CSR reputation. Yet, for a brand with a CA reputation, the effect of perceived fit was not found. These results may reflect early attention resources engagement and altruistic motivation at the late stage during brand extension evaluation. The findings provided neurological evidence for which of the two types of brand reputation (CSR vs. CA) have a more positive effect on brand extension.